Silver powder and preparation method and application thereof
By using spherical silver powder formed by stacking single crystal silver powder of large particles and small particles and controlling its particle size and dispersion, the problems of large particle size and poor dispersion in the existing silver powder preparation methods are solved, and the performance of electromagnetic wave shielding sheets is significantly improved.
Patent Information
- Application Number
- CN202411963463.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
AI Technical Summary
The existing methods for preparing ultrafine silver powder have problems such as large particle size, narrow particle size distribution, poor dispersion and stability, resulting in poor conductivity and electromagnetic wave shielding performance of electromagnetic wave shielding sheets.
The spherical silver powder composed of large-grain single-crystal silver powder and small-grain single-crystal silver powder is used to control the average particle size of large and small particles, and the dispersion and particle size distribution range of silver powder are improved by adjusting the SPAN value and root mean square roughness of the silver powder.
The silver powder has the characteristics of smooth surface, small particle size, wide particle size distribution range and good dispersion, and the conductive performance and electromagnetic wave shielding performance of the electromagnetic wave shielding sheet are improved.
Smart Images

Figure CN119772164A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal powders, in particular to silver powder and a preparation method and application thereof. Background Art
[0002] Electromagnetic wave shielding sheets are made by adding certain single metal component materials or multi-metal component composite materials to inhibit electromagnetic waves from penetrating the surface of the device or entering the inside of the device, thereby shielding electromagnetic radiation. Therefore, electromagnetic wave shielding sheets are widely used in the production and manufacturing of various electronic products, such as solar panels, smart phones, tablets, TVs and computer monitors.
[0003] Ultrafine silver powder can effectively inhibit the propagation of electromagnetic waves and achieve the purpose of shielding signals due to its unique conductivity and oxidation resistance. Therefore, it is widely used in the preparation of electromagnetic wave shielding sheets. However, the ultrafine silver powder prepared by the existing preparation method has many problems such as large particle size, narrow particle size distribution, poor dispersibility and stability. When the ultrafine silver powder is unevenly distributed in the matrix, the conductive path will be blocked, resulting in poor conductivity and electromagnetic wave shielding performance of the electromagnetic wave shielding sheet. Summary of the invention
[0004] Based on this, it is necessary to provide a silver powder and its preparation method and application to address the above problems. The silver powder has the characteristics of smooth surface, small particle size, wide particle size distribution range and good dispersibility, which can enable it to prepare electromagnetic wave shielding thin sheets with excellent conductive properties and electromagnetic wave shielding properties.
[0005] A silver powder is spherical and is formed by stacking large-grained single-crystal silver powder and small-grained single-crystal silver powder, wherein the average particle size of the large-grained single-crystal silver powder in the silver powder is 0.8μm-1.2μm, the average particle size of the small-grained single-crystal silver powder is 0.3μm-0.6μm, and the SPAN of the silver powder is 6.45-8.3, and the root mean square roughness is 2.36nm-3.97nm.
[0006] In one embodiment, the mass fraction of large-particle single-crystal silver powder in the silver powder is 30.4%-45.3%, and the mass fraction of small-particle single-crystal silver powder is 54.7%-69.6%.
[0007] The silver powder of the present invention is a spherical particle formed by stacking large-particle single-crystal silver powder and small-particle single-crystal silver powder of different particle sizes, and the average particle size of the large-particle single-crystal silver powder and the small-particle single-crystal silver powder is controlled, so that the small-particle single-crystal silver powder can be filled in the pores formed between the large-particle single-crystal silver powder to improve the overall conductive circuit of the silver powder, and the silver powder has a smaller particle size and good dispersibility; at the same time, by controlling the root mean square roughness of the silver powder, the silver powder has a smooth surface, which can further improve the dispersibility of the silver powder; in addition, by controlling the SPAN value of the silver powder, the particle size distribution range of the silver powder is wide. Therefore, the silver powder of the present invention has the characteristics of smooth surface, small particle size, wide particle size distribution range, and good dispersibility, and can be used to prepare an electromagnetic wave shielding sheet with excellent conductive performance and electromagnetic wave shielding performance.
[0008] A method for preparing the silver powder as described above comprises the following steps:
[0009] Under stirring conditions, mixing a first reducing agent solution and a second reducing agent solution, then adding a regulating agent solution to adjust the pH to 8-10, and then sequentially adding a silver nitrate solution and a dispersant solution to obtain a reaction solution, wherein the reducing property of the first reducing agent in the first reducing agent solution is greater than the reducing property of the second reducing agent in the second reducing agent solution;
[0010] The reaction liquid is subjected to solid-liquid separation and heating treatment to obtain silver powder, wherein the heating treatment conditions include: heating to 100°C-600°C at a rate of 2°C / min-15°C / min, and heat preservation treatment for 1h-6h.
[0011] In one embodiment, the mass ratio of silver nitrate, the first reducing agent, the second reducing agent and the regulator is (2-30):(1.5-3):(0.5-2):(0.3-1);
[0012] And / or, the mass ratio of silver nitrate to dispersant is 1:0.01-1.
[0013] In one embodiment, the mass concentration of the silver nitrate solution is 200g / L-350g / L;
[0014] And / or, the mass concentrations of the first reducing agent solution and the second reducing agent solution are independently selected from 10 g / L-100 g / L;
[0015] And / or, the mass fraction of the regulator in the regulator solution is 2.3%-12%;
[0016] And / or, the mass concentration of the dispersant solution is 1g / L-5g / L.
[0017] In one embodiment, the first reducing agent solution and the second reducing agent solution are independently selected from at least one of ascorbic acid solution, hydrazine hydrate solution, hydroquinone solution, organic amine solution, glucose solution, formaldehyde solution, acetaldehyde solution, iron solution, and sodium borohydride solution;
[0018] And / or, the conditioning agent solution is selected from at least one of sodium hydroxide solution, sodium carbonate solution, ammonia solution, nitric acid solution and sulfuric acid solution;
[0019] And / or, the dispersant is at least one selected from polyvinyl alcohol, polyacrylic acid, gelatin, polyethylene glycol, gum arabic, polyvinyl pyrrolidone, sodium lauryl sulfate, lecithin, and stearic acid.
[0020] In one embodiment, in the step of sequentially adding the silver nitrate solution and the dispersant solution, after the silver nitrate solution is added to react for 3 min-10 min, the dispersant solution is added to continue reacting for 2 h-5 h, wherein the dispersant solution is added dropwise at a uniform speed within 2 min-5 min.
[0021] The preparation method of the silver powder of the present invention can effectively regulate the rate of the redox reaction and control the morphology and size of the silver powder by controlling the order of adding the components and the pH value of the reaction system and controlling the reducing properties of the first reducing agent and the second reducing agent. At the same time, the morphology and size of the silver powder can be further controlled by utilizing the capping and coating effects of the added dispersant on the silver powder, and the dispersibility between the silver powder particles can be improved. In addition, by synergistically controlling the conditions of the heat treatment, the morphology and size of the silver powder can be further controlled, and finally a spherical silver powder with large and small particles doped, smooth surface, wide particle size distribution range and good dispersibility can be obtained.
[0022] A method for preparing an electromagnetic wave shielding sheet comprises the following steps:
[0023] The silver powder, organic matrix material, curing agent and diluent as described above are mixed to obtain silver powder slurry; and then the silver powder slurry is made into an electromagnetic wave shielding sheet through a casting process.
[0024] The preparation method of the electromagnetic wave shielding thin sheet of the present invention, by adopting the silver powder of the present invention, can make the prepared electromagnetic wave shielding thin sheet have excellent conductive performance and electromagnetic wave shielding performance; at the same time, compared with the traditional electrospinning technology, the preparation method adopts the casting method, which is not only simple in process and easy to operate, but also low in cost.
[0025] An electromagnetic wave shielding sheet is prepared by the method for preparing the electromagnetic wave shielding sheet as described above.
[0026] An electronic product prepared using the electromagnetic wave shielding sheet as described above. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 is a scanning electron microscope image of the silver powder prepared in Example 1 of the present invention;
[0029] Figure 2 is the X-ray diffraction pattern of the silver powder prepared in Example 1 of the present invention;
[0030] Figure 3 This is a distribution diagram of silver elements in a cross section of the electromagnetic wave shielding sheet prepared in Example 1 of the present invention;
[0031] Figure 4 is the electromagnetic shielding effectiveness curve of the electromagnetic wave shielding sheet prepared in Example 1 of the present invention;
[0032] Figure 5 This is a scanning electron microscope image of the silver powder prepared in Comparative Example 6 of the present invention;
[0033] Figure 6 This is a scanning electron microscope image of the silver powder prepared in Comparative Example 8 of the present invention. DETAILED DESCRIPTION
[0034] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0036] The silver powder provided by the present invention is spherical, and is formed by stacking large-particle single-crystal silver powder and small-particle single-crystal silver powder, wherein the average particle size of the large-particle single-crystal silver powder in the silver powder is 0.8μm-1.2μm, and the average particle size of the small-particle single-crystal silver powder is 0.3μm-0.6μm, and the SPAN of the silver powder is 6.45-8.3, and the root mean square roughness is 2.36nm-3.97nm.
[0037] In the present invention, the silver powder is a spherical particle formed by stacking large-particle single-crystal silver powder and small-particle single-crystal silver powder of different particle sizes, and the average particle size of the large-particle single-crystal silver powder and the small-particle single-crystal silver powder is controlled, so that the small-particle single-crystal silver powder can be filled in the pores formed between the large-particle single-crystal silver powder to improve the overall conductive circuit of the silver powder, and the silver powder has a smaller particle size and good dispersibility; at the same time, by controlling the root mean square roughness of the silver powder, the silver powder has a smooth surface, which can further improve the dispersibility of the silver powder; in addition, by controlling the SPAN value of the silver powder, the particle size distribution range of the silver powder is wide. Therefore, the silver powder of the present invention has the characteristics of smooth surface, small particle size, wide particle size distribution range, and good dispersibility, and can be used to prepare an electromagnetic wave shielding sheet with excellent conductivity and electromagnetic wave shielding performance.
[0038] In addition, it should be explained that in the present invention, by controlling the root mean square roughness of the silver powder, the contact line pinning effect existing at the solid-liquid interface can be effectively reduced in the subsequent process of preparing the electromagnetic wave shielding sheet, that is, when the silver powder and the organic matrix material are combined, which is beneficial to improving the interfacial adhesion between the silver powder particles and the organic matrix material, and improving the bonding force between the silver powder particles and the organic matrix material.
[0039] Furthermore, in the present invention, an atomic force microscope (AFM) is used to test the root mean square roughness (Rq) of the silver powder. The root mean square roughness refers to the root mean square value between the high and low surfaces of the material. In the present invention, the root mean square roughness of the silver powder is used to characterize the surface roughness of the silver powder, that is, the surface smoothness.
[0040] Optionally, the mass fraction of large-particle single-crystal silver powder in the silver powder is 30.4%-45.3%, preferably 42.8%, and the mass fraction of small-particle single-crystal silver powder is 54.7%-69.6%, preferably 57.2%. Such an arrangement can further improve the uniformity of large and small particle doping in the silver powder, which is conducive to the silver powder to construct a more complete conductive circuit, thereby improving the conductivity and electromagnetic wave shielding performance of the electromagnetic wave shielding sheet.
[0041] At the same time, the present invention also provides a method for preparing the silver powder as described above, comprising the following steps:
[0042] S1, under stirring conditions, mixing a first reducing agent solution and a second reducing agent solution, then adding a regulating agent solution to adjust the pH to 8-10, and then sequentially adding a silver nitrate solution and a dispersant solution to obtain a reaction solution, wherein the reducing property of the first reducing agent in the first reducing agent solution is greater than the reducing property of the second reducing agent in the second reducing agent solution;
[0043] S2, subjecting the reaction liquid to solid-liquid separation and heat treatment to obtain silver powder, wherein the heating treatment conditions include: heating to 100°C-600°C at a rate of 2°C / min-15°C / min, and heat preservation treatment for 1h-6h.
[0044] In step S1, by limiting the order of adding each component, and by adding a regulator solution to control the pH of the reaction system to 8-10, the first reducing agent can be used to preferentially react with silver nitrate to generate black elemental silver by utilizing the fact that the reducing power of the first reducing agent is greater than that of the second reducing agent. As the reaction proceeds, the content of the first reducing agent and the pH of the system will change. At this time, the second reducing agent will react with the silver nitrate together with the first reducing agent to form elemental silver by oxidation-reduction reaction, and jointly provide the nucleation and growth source of the silver powder. The silver elemental reduced by the second reducing agent will provide a part for the growth of the nucleated silver ions, and a part for nucleation. In this process, some grains will not have time to grow, thereby obtaining mixed silver powder particles doped with large and small particles. Moreover, the addition of the second reducing agent will also reduce the speed of the first reducing agent reducing the silver particles in the entire oxidation reaction process to a certain extent, avoiding the phenomenon of agglomeration between the silver powder particles due to excessively fast reaction speed resulting in too many nuclei.
[0045] At the same time, by adding a dispersant after adding the silver nitrate solution, the capping and coating effects of the dispersant on silver atoms can be utilized. On the one hand, by selectively adsorbing the dispersant on a certain crystal plane of the silver particles, the growth of silver crystals along the crystal plane can be effectively inhibited, the morphology of the silver powder can be controlled, and silver powders with different morphologies can be obtained; on the other hand, during the growth of the crystals, the unique hydrophilic and lipophilic groups of the dispersant will also be wrapped on the surface of the silver particles, so that a steric hindrance effect is generated between the silver particles, and then the silver particles will slide and stagger when they meet, effectively avoiding the aggregation of the silver particles due to van der Waals forces, thereby preparing ultrafine silver powder with good dispersibility.
[0046] In addition, in step S2, by limiting the heating treatment conditions, on the one hand, the dispersant on the surface of the silver particles can be effectively removed, avoiding the problem of poor conductive circuit constructed between the silver particles caused by the formation of an insulating coating layer on the surface of the silver particles by the dispersant, which is beneficial to further improve the conductivity and electromagnetic shielding performance of the electromagnetic wave shielding sheet; on the other hand, the branched structure on the surface of the silver particles can undergo solid-state diffusion and fusion with the matrix particles, so that the morphology and dispersibility of the silver powder are significantly changed, and the smoothness and dispersibility of the surface of the silver powder particles are improved, and finally spherical silver powder with large and small particles doped, small particle size, smooth surface, wide particle size distribution range and good dispersibility is obtained.
[0047] In step S1, in the step of sequentially adding the silver nitrate solution and the dispersant solution, after the silver nitrate solution is added and reacted for 3 min-10 min, the dispersant solution is added and reacted for 2 h-5 h, wherein the dispersant solution is added dropwise at a uniform speed within 2 min-5 min. Such an arrangement is conducive to further controlling the morphology and growth of the silver powder particles, and better obtaining silver powder particles with a mixture of large and small single crystal silver powder.
[0048] Optionally, the mass ratio of silver nitrate, the first reducing agent, the second reducing agent and the regulator is (2-30):(1.5-3):(0.5-2):(0.3-1); by such an arrangement, the rate of the redox reaction between silver nitrate and the first reducing agent and the second reducing agent can be better regulated by adjusting the mass ratio of silver nitrate, the first reducing agent, the second reducing agent and the regulator, and the morphology and growth size of the silver powder can be further controlled, which is conducive to better obtaining a mixed silver powder doped with large and small particles.
[0049] Optionally, the mass ratio of silver nitrate to dispersant is 1:0.01-1. Such a configuration is conducive to better control of the morphology of silver powder and the dispersibility between particles.
[0050] Optionally, the mass concentration of the silver nitrate solution is 200g / L-350g / L.
[0051] Optionally, the mass concentration of the first reducing agent solution is 10 g / L-100 g / L; the mass concentration of the second reducing agent solution is 10 g / L-100 g / L.
[0052] In the present invention, by controlling the mass concentrations of the silver nitrate solution, the first reducing agent solution and the second reducing agent solution, it is beneficial to control the rate of the redox reaction between the silver nitrate and the reducing agent, thereby better controlling the morphology and size of the silver powder.
[0053] Further, the first reducing agent solution and the second reducing agent solution are independently selected from at least one of ascorbic acid solution, hydrazine hydrate solution, hydroquinone solution, organic amine solution, glucose solution, formaldehyde solution, acetaldehyde solution, iron solution, and sodium borohydride solution; preferably, the first reducing agent solution is selected from at least one of ascorbic acid solution, hydrazine hydrate solution, iron solution, sodium borohydride solution, and hydroquinone solution, preferably ascorbic acid solution; the second reducing agent solution is selected from at least one of glucose solution, formaldehyde solution, acetaldehyde solution, and organic amine solution.
[0054] Further preferably, the first reducing agent solution is selected from ascorbic acid solution, and the second reducing agent solution is selected from glucose solution. In this configuration, the present invention uses glucose and ascorbic acid as reducing agents together. It can be understood that since ascorbic acid contains a strongly reducing dienol, it will preferentially react with silver nitrate to generate black elemental silver. When the pH of the reaction system changes, hydroxide ions can be provided to glucose to react with silver ammonia to reduce elemental silver, thereby forming large and small particle-doped silver powder particles. At the same time, the entire preparation process is environmentally friendly and non-toxic, and large and small particle-doped silver powder can be prepared at room temperature.
[0055] In one embodiment, silver nitrate and deionized water are prepared into a silver nitrate solution at room temperature.
[0056] In one embodiment, the first reducing agent solution is prepared by mixing the first reducing agent solution and deionized water at room temperature; similarly, the second reducing agent solution is prepared by mixing the second reducing agent solution and deionized water at room temperature.
[0057] Optionally, the mass fraction of the regulator in the regulator solution is 2.3%-12%; such a setting can better regulate the pH value of the reaction system, thereby controlling the rate of the redox reaction, which is conducive to better controlling the morphology and size of the silver powder.
[0058] Furthermore, the regulator solution is selected from at least one of sodium hydroxide solution, sodium carbonate solution, ammonia solution, nitric acid solution and sulfuric acid solution.
[0059] In one embodiment, a conditioning agent solution is prepared by mixing a conditioning agent and deionized water at room temperature.
[0060] Optionally, the mass concentration of the dispersant solution is 1 g / L-5 g / L; such a setting can further effectively avoid agglomeration between the silver particles generated by the reaction, and is also conducive to further controlling the morphology and growth direction of the silver particles.
[0061] Furthermore, the dispersant is selected from at least one of polyvinyl alcohol, polyacrylic acid, gelatin, polyethylene glycol, gum arabic, polyvinyl pyrrolidone, sodium lauryl sulfate, lecithin, and stearic acid.
[0062] In one embodiment, the dispersant solution is prepared by mixing the conditioning agent and deionized water at room temperature.
[0063] In one embodiment, the first reducing agent solution and the second reducing agent solution are mixed for 5-20 minutes under stirring conditions, and then the adjusting agent solution is added and mixed for 5-20 minutes and the pH is adjusted to 8-10, and then the silver nitrate solution and the dispersant solution are added in sequence. This arrangement is conducive to improving the mixing uniformity of each solution.
[0064] It can be understood that the entire step S1 of the present invention is carried out under stirring conditions. On the one hand, it can promote the mixing uniformity between the solutions, so that the reaction during the redox reaction is more sufficient and complete. On the other hand, it can make the generated silver particles evenly dispersed in the reaction system to prevent the silver particles from agglomerating. In addition, the dispersant can be more fully coated on the specific crystal planes of the silver particles, inhibiting the growth of the silver particles on the crystal planes, thereby better controlling the morphology of the silver particles, so that the particle size of the small particles formed can be filled in the pores formed between the large particles of silver powder.
[0065] In step S2, after the reaction liquid is subjected to solid-liquid separation and heat treatment, the silver powder after the heat treatment is placed in an oscillator for 1h-8h to obtain silver powder.
[0066] In one embodiment, the solid-liquid separation step includes: removing the supernatant after the reaction by sedimentation of the reaction solution, transferring the remaining part into a cleaning bucket, and then washing with deionized water and ethanol for 3 to 4 times, and filtering to remove water.
[0067] Therefore, the preparation method of the silver powder of the present invention can effectively regulate the rate of the redox reaction and control the morphology and size of the silver powder by controlling the order of adding the components and the pH value of the reaction system, and controlling the reducing properties of the first reducing agent and the second reducing agent. At the same time, the morphology and size of the silver powder can be further controlled by the capping and coating effects of the added dispersant on the silver powder, and the dispersibility between the silver powder particles can be improved; in addition, by synergistically controlling the conditions of the heat treatment, the morphology and size of the silver powder can be further controlled, and finally a spherical silver powder with large and small particles doped, smooth surface, wide particle size distribution range and good dispersibility is obtained.
[0068] In addition, the present invention also provides a method for preparing an electromagnetic wave shielding sheet, comprising the following steps:
[0069] The silver powder, organic matrix material, curing agent and diluent as described above are mixed to obtain silver powder slurry; and then the silver powder slurry is made into an electromagnetic wave shielding sheet through a casting process.
[0070] Specifically, silver powder, organic matrix material and curing agent are mixed, and then a diluent is added. After being fully mixed under a high-speed stirrer, the mixture is placed in an ultrasonic instrument for ultrasonication to obtain a uniformly mixed silver powder slurry. After standing for 1h-2h, the slurry is poured into a mold, and after waiting for 24h-56h, an electromagnetic wave shielding sheet is obtained.
[0071] In one embodiment, the mass ratio of the silver powder, the organic matrix material, the curing agent and the diluent is (3-10): (5-13): (1-3): (1.5-2); such a configuration can be used to adjust the mass ratio of the silver powder, the curing agent and the diluent, which is conducive to obtaining an electromagnetic wave shielding sheet with better conductive properties and electromagnetic wave shielding properties.
[0072] In one embodiment, the organic matrix material is selected from at least one of epoxy resin, phenolic resin, polyamide resin, polyphenylene sulfide, silicone rubber, and polyacrylonitrile.
[0073] In one embodiment, the curing agent is selected from at least one of polyamide resin, triethylenetetramine, B-hydroxyethylethylenediamine, silicone rubber, epoxy resin, and polyisocyanate.
[0074] In one embodiment, the diluent is selected from at least one of ethanol, formaldehyde, xylene, rosin water, and banana water.
[0075] The preparation method of the electromagnetic wave shielding thin sheet of the present invention, by adopting the silver powder of the present invention, can make the prepared electromagnetic wave shielding thin sheet have excellent conductive performance and electromagnetic wave shielding performance; at the same time, compared with the traditional electrospinning technology, the preparation method adopts the casting method, which is not only simple in process and easy to operate, but also low in cost.
[0076] Furthermore, the present invention provides an electromagnetic wave shielding sheet prepared by the method for preparing the electromagnetic wave shielding sheet as described above. The electromagnetic wave shielding sheet has excellent electrical conductivity and electromagnetic wave shielding performance. Specifically, the conductivity of the electromagnetic wave shielding sheet can reach more than 804 (S / m), and the electromagnetic wave shielding performance is as high as about 71dB.
[0077] The present invention also provides an electronic product prepared by using the electromagnetic wave shielding sheet as described above.
[0078] In one embodiment, the electronic product may be a solar cell substrate, a smart phone, a tablet computer, a television, a computer monitor, etc.
[0079] The silver powder, its preparation method and application will be further described below by the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0080] It should be noted that the epoxy resin A involved in the examples and comparative examples of the present invention is mainly used as an organic matrix material, and the epoxy resin B is mainly used as a semi-curing agent.
[0081] Example 1
[0082] 15 kg of silver nitrate is dissolved in 50 L of deionized water at room temperature to obtain a silver nitrate solution; 5.4 kg of ascorbic acid is dissolved in 100 L of deionized water at room temperature to obtain a first reducing agent solution; 1.8 kg of glucose is dissolved in 100 L of deionized water at room temperature to obtain a second reducing agent solution; 30 g of polyvinyl pyrrolidone is dissolved in 10 L of deionized water at room temperature to obtain a dispersant solution.
[0083] Under stirring conditions, the 3L first reducing agent solution and 3L second reducing agent solution obtained above were mixed for 15 minutes, and then 2kg of 8% ammonia solution by mass was added and mixed for 15 minutes to obtain a mixed solution with a pH of about 9.2. Then, the 10L silver nitrate solution obtained above was added to the mixed solution and reacted for 5 minutes. Then, the 0.3L dispersant solution obtained above was added and the reaction was continued for 3 hours, wherein the time for uniformly adding the dispersant solution was 3 minutes to obtain a reaction solution.
[0084] The reaction solution obtained above was removed from the upper clear liquid after the reaction by sedimentation, and the remaining part was transferred to a cleaning bucket, washed with deionized water and ethanol for 3 times, and filtered to remove water to obtain a crude product; then the crude product was placed in a muffle furnace, heated to 100°C at a rate of 5°C / min, and kept warm for 5.5 hours, and then placed on an oscillator for 2 hours to obtain silver powder.
[0085] At room temperature, the above-obtained 2kg of silver powder, 3kg of epoxy resin A (model YT-CC302S (slow-drying type)) and 1kg of epoxy resin B (model YT-CC302S (slow-drying type)) and 5L of ethanol were mixed and stirred evenly under a high-speed stirrer, and then transferred to an ultrasonic instrument for ultrasonication. The operation was repeated 4 times. After standing for 30 minutes, the bubbles were removed and poured into 100 rectangular molds, waiting for molding. After standing for 56 hours, an electromagnetic wave shielding sheet was obtained.
[0086] Example 2
[0087] The only difference between Example 2 and Example 1 is that polyethylene glycol is used instead of polyvinyl pyrrolidone of equal mass; the temperature is raised to 400°C at a rate of 8°C / min and kept warm for 2h, while the other conditions are the same, to obtain silver powder; then at room temperature, the above-obtained 7.5kg of silver powder, 6kg of epoxy resin A (model YT-CC302S (slow-drying type)) and 2kg of epoxy resin B (model YT-CC302S (slow-drying type)) and 5L of ethanol are mixed, and stirred evenly under a high-speed stirrer, while the other conditions are the same, to obtain an electromagnetic wave shielding sheet.
[0088] Example 3
[0089] Compared with Example 1, Example 3 differs only in that stearic acid and polyvinyl alcohol are used to replace an equal amount of polyvinyl pyrrolidone, wherein the mass ratio of stearic acid to polyvinyl alcohol is 2:0.5; the temperature is raised to 350°C at a rate of 11°C / min, and the heat treatment is carried out for 2.5 hours, while the other conditions are the same, to obtain silver powder; then at room temperature, the above-obtained 6kg of silver powder, 6kg of epoxy resin A (model YT-CC302S (slow-drying type)) and 2kg of epoxy resin B (model YT-CC302S (slow-drying type)) and 5L of ethanol are mixed, and stirred evenly under a high-speed stirrer, while the other conditions are the same, to obtain an electromagnetic wave shielding sheet.
[0090] Example 4
[0091] The only difference between Example 4 and Example 1 is that the mass of polyvinyl pyrrolidone is 20 g, and the other conditions are the same, and silver powder and the corresponding electromagnetic wave shielding sheet are obtained.
[0092] Example 5
[0093] The only difference between Example 5 and Example 1 is that 10 kg of silver nitrate is dissolved in 50 L of deionized water at room temperature to obtain a silver nitrate solution; 3.1 kg of ascorbic acid is dissolved in 100 L of deionized water at room temperature to obtain a first reducing agent solution; 1 kg of glucose is dissolved in 100 L of deionized water at room temperature to obtain a second reducing agent solution; 20 g of polyvinyl pyrrolidone is dissolved in 10 L of deionized water at room temperature to obtain a dispersant solution.
[0094] Under stirring conditions, the 1.3L first reducing agent solution and 0.5L second reducing agent solution obtained above were mixed for 15 minutes, and then 0.5kg of 5% ammonia solution by mass was added and mixed for 15 minutes to obtain a mixed solution with a pH of about 9.4. Then, the 3L silver nitrate solution obtained above was added to the mixed solution and reacted for 5 minutes. Then, the 0.12L dispersant solution obtained above was added and the reaction was continued for 3 hours, wherein the time for uniform dripping of the dispersant solution was 2 minutes to obtain a reaction solution, and the other conditions were the same to obtain silver powder and the corresponding electromagnetic wave shielding sheet.
[0095] Example 6
[0096] The only difference between Example 6 and Example 1 is that 16 kg of silver nitrate is dissolved in 50 L of deionized water at room temperature to obtain a silver nitrate solution; 6 kg of ascorbic acid is dissolved in 100 L of deionized water at room temperature to obtain a first reducing agent solution; 3 kg of glucose is dissolved in 100 L of deionized water at room temperature to obtain a second reducing agent solution; 38 g of polyvinyl pyrrolidone is dissolved in 10 L of deionized water at room temperature to obtain a dispersant solution.
[0097] Under stirring conditions, the 3.1L first reducing agent solution and 1.2L second reducing agent solution obtained above were mixed for 15 minutes, and then 3.1kg of 10% ammonia solution by mass was added and mixed for 15 minutes to obtain a mixed solution with a pH of about 8.5. Then, the 22L silver nitrate solution obtained above was added to the mixed solution and reacted for 5 minutes. Then, the 0.6L dispersant solution obtained above was added and the reaction was continued for 3 hours. The time for the uniform dripping of the dispersant solution was 5 minutes to obtain a reaction solution. The other conditions were the same to obtain silver powder and the corresponding electromagnetic wave shielding sheet.
[0098] Example 7
[0099] The only difference between Example 7 and Example 1 is that, under stirring conditions, 1L of the first reducing agent solution and 0.2L of the second reducing agent solution obtained above are mixed for 15 minutes, and then 3kg of 8% ammonia solution by mass is added and mixed for 15 minutes to obtain a mixed solution with a pH of about 8.8, and then the 14L of silver nitrate solution obtained above is added to the mixed solution to react for 5 minutes, and then the 0.3L of dispersant solution obtained above is added to continue the reaction for 3 hours, and the other conditions are the same to obtain silver powder and the corresponding electromagnetic wave shielding sheet.
[0100] Example 8
[0101] The only difference between Example 8 and Example 1 is that 20 kg of silver nitrate is dissolved in 50 L of deionized water at room temperature to obtain a silver nitrate solution, and the other conditions are the same to obtain silver powder and the corresponding electromagnetic wave shielding sheet.
[0102] Example 9
[0103] The only difference between Example 9 and Example 1 is that hydrazine hydrate is used instead of ascorbic acid, and acetaldehyde is used instead of glucose. The other conditions are the same, and silver powder and the corresponding electromagnetic wave shielding sheet are obtained.
[0104] Example 10
[0105] The only difference between Example 10 and Example 1 is that after adding the 10L silver nitrate solution obtained above to the mixed solution and reacting for 2 minutes, the 0.3L dispersant solution obtained above is added and the reaction is continued for 3 hours. The other conditions are the same to obtain silver powder and the corresponding electromagnetic wave shielding sheet.
[0106] Embodiment 11
[0107] The only difference between Example 11 and Example 1 is that the time for uniformly dropping the dispersant solution is 1 min, and the other conditions are the same to obtain silver powder and the corresponding electromagnetic wave shielding sheet.
[0108] Example 12
[0109] The only difference between Example 12 and Example 1 is that the time for uniformly dropping the dispersant solution is 7 minutes, and the other conditions are the same, and silver powder and the corresponding electromagnetic wave shielding sheet are obtained.
[0110] Comparative Example 1
[0111] The only difference between Comparative Example 1 and Example 1 is that, under stirring conditions, 3L of the first reducing agent solution and 3L of the second reducing agent solution obtained above are mixed for 15 minutes, and then 1.1kg of 8% ammonia solution is added and mixed for 15 minutes to obtain a mixed solution with a pH of about 7. The other conditions are the same, and silver powder and the corresponding electromagnetic wave shielding sheet are obtained.
[0112] Comparative Example 2
[0113] The only difference between Comparative Example 2 and Example 1 is that, under stirring conditions, 3L of the first reducing agent solution and 3L of the second reducing agent solution obtained above are mixed for 15 minutes, and then 3.7kg of 8% ammonia solution is added and mixed for 15 minutes to obtain a mixed solution with a pH of about 11. The other conditions are the same, and silver powder and the corresponding electromagnetic wave shielding sheet are obtained.
[0114] Comparative Example 3
[0115] The only difference between Comparative Example 3 and Example 1 is that 1.8 kg of ascorbic acid is dissolved in 100 L of deionized water at room temperature to obtain a second reducing agent solution, and the other conditions are the same to obtain silver powder and the corresponding electromagnetic wave shielding sheet.
[0116] Comparative Example 4
[0117] The difference between Comparative Example 4 and Example 1 is that 10 L of the silver nitrate solution and 0.3 L of the dispersant solution obtained above are added to the mixed solution at the same time and the reaction is continued for 3 h. The other conditions are the same to obtain silver powder and the corresponding electromagnetic wave shielding sheet.
[0118] Comparative Example 5
[0119] The only difference between Comparative Example 5 and Example 1 is that 0.3 L of the dispersant solution obtained above is added to the mixed solution for 5 minutes, and then 10 L of the silver nitrate solution obtained above is added to react for 3.5 hours. The other conditions are the same to obtain silver powder and the corresponding electromagnetic wave shielding sheet.
[0120] Comparative Example 6
[0121] The only difference between Comparative Example 6 and Example 1 is that the temperature is raised to 80° C. at a rate of 10° C. / min and the heat treatment is carried out for 6 hours. The other conditions are the same, and an electromagnetic wave shielding sheet is obtained.
[0122] Comparative Example 7
[0123] Compared with Example 1, Comparative Example 7 differs only in that the temperature is raised to 800° C. at a rate of 30° C. / min and the heat treatment is carried out for 0.5 h. Other conditions are the same, and an electromagnetic wave shielding sheet is obtained.
[0124] Comparative Example 8
[0125] The only difference between Comparative Example 8 and Example 1 is that the temperature is raised to 100° C. at a rate of 1° C. / min and the heat treatment is carried out for 7 hours. The other conditions are the same, and an electromagnetic wave shielding sheet is obtained.
[0126] The morphology structure of the silver powder prepared in Examples 1-12 and Comparative Examples 1-8, the mass fraction of large-particle single-crystal silver powder and small-particle single-crystal silver powder in the silver powder, the SPAN of the silver powder, and the root mean square roughness were tested, and the test results are shown in Table 1. At the same time, the performance of the electromagnetic wave shielding sheets prepared in Examples 1-12 and Comparative Examples 1-8 was tested, and the test results are shown in Table 1, wherein the test method is specifically as follows:
[0127] The morphology and size structure test of silver powder was carried out by scanning electron microscope.
[0128] The mass fractions of large-particle single-crystalline silver powder and small-particle single-crystalline silver powder in the silver powder are obtained by sieving the large particles and the small particles, and then weighing them separately using a precision balance.
[0129] SPAN of silver powder: Using laser particle size analyzer to test the SPAN of silver powder 50 , D 90 and D 10 , and then according to the calculation formula: SPAN = (D 90 -D 10 ) / D 50 Calculated.
[0130] Root mean square roughness: The root mean square roughness of the silver powder particles was tested using an atomic force microscope (AFM).
[0131] Conductivity test of electromagnetic wave shielding sheet: The test is carried out using a four-probe resistivity tester, and then calculated using the calculation formula: conductivity σ=1 / ρ, where ρ is the resistivity.
[0132] Electromagnetic wave shielding performance test of electromagnetic wave shielding sheet: test is carried out using vector network analyzer.
[0133] from Figure 1 It can be seen from the figure that the silver powder prepared in Example 1 is spherical, and the silver powder is formed by the accumulation of large-particle single-crystal silver powder and small-particle single-crystal silver powder; Figure 2 It can be seen from the X-ray diffraction analysis curve corresponding to the silver powder prepared in Example 1 of the present invention that there are no obvious diffraction peaks of oxides and impurities, and the peak positions of the diffraction peaks correspond to the (111), (200), (311), and (220) crystal planes of the face-centered cubic structure Ag, respectively, indicating that the substance prepared in Example 1 of the present invention is a single substance of silver, and the silver particles are not oxidized and have high purity; Figure 3 It can be seen that the silver particles are evenly distributed in the organic matrix material and can form an effective conductive circuit; Figure 4 It can be seen that the shielding performance of the electromagnetic wave shielding sheet prepared in Example 1 reaches 71dB, which has excellent electromagnetic wave shielding performance; Figure 5 It can be seen that due to the inappropriate heat treatment temperature in Comparative Example 6, the morphology of the prepared silver powder is strip-shaped; Figure 6 It can be seen that the silver powder prepared in Comparative Example 8 is flower-shaped and has a high surface roughness.
[0134] Table 1
[0135]
[0136] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0137] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A silver powder, characterized in that: The silver powder is spherical, and is formed by the accumulation of large-particle single-crystal silver powder and small-particle single-crystal silver powder. The average particle size of the large-particle single-crystal silver powder in the silver powder is 0.8μm-1.2μm, and the average particle size of the small-particle single-crystal silver powder is 0.3μm-0.6μm. The SPAN of the silver powder is 6.45-8.3, and the root mean square roughness is 2.36nm-3.97nm.
2. The silver powder according to claim 1, characterized in that The mass fraction of the large-particle single-crystal silver powder in the silver powder is 30.4%-45.3%, and the mass fraction of the small-particle single-crystal silver powder is 54.7%-69.6%.
3. A method for preparing the silver powder according to claim 1 or 2, characterized in that: The steps include: Under stirring conditions, mixing a first reducing agent solution and a second reducing agent solution, then adding a regulating agent solution to adjust the pH to 8-10, and then sequentially adding a silver nitrate solution and a dispersant solution to obtain a reaction solution, wherein the reducing property of the first reducing agent in the first reducing agent solution is greater than the reducing property of the second reducing agent in the second reducing agent solution; The reaction liquid is subjected to solid-liquid separation and heating treatment to obtain silver powder, wherein the heating treatment conditions include: heating to 100°C-600°C at a rate of 2°C / min-15°C / min, and heat preservation treatment for 1h-6h.
4. The method for preparing silver powder according to claim 3, characterized in that: The mass ratio of silver nitrate, the first reducing agent, the second reducing agent and the adjusting agent is (2-30):(1.5-3):(0.5-2):(0.3-1); And / or, the mass ratio of silver nitrate to dispersant is 1:0.01-1.
5. The method for preparing silver powder according to claim 3 or 4, characterized in that: The mass concentration of the silver nitrate solution is 200g / L-350g / L; And / or, the mass concentrations of the first reducing agent solution and the second reducing agent solution are independently selected from 10 g / L-100 g / L; And / or, the mass fraction of the regulator in the regulator solution is 2.3%-12%; And / or, the mass concentration of the dispersant solution is 1g / L-5g / L.
6. The method for preparing silver powder according to claim 3 or 4, characterized in that: The first reducing agent solution and the second reducing agent solution are independently selected from at least one of ascorbic acid solution, hydrazine hydrate solution, hydroquinone solution, organic amine solution, glucose solution, formaldehyde solution, acetaldehyde solution, iron solution, and sodium borohydride solution; And / or, the conditioning agent solution is selected from at least one of sodium hydroxide solution, sodium carbonate solution, ammonia solution, nitric acid solution and sulfuric acid solution; And / or, the dispersant is at least one selected from polyvinyl alcohol, polyacrylic acid, gelatin, polyethylene glycol, gum arabic, polyvinyl pyrrolidone, sodium lauryl sulfate, lecithin, and stearic acid.
7. The method for preparing silver powder according to claim 3 or 4, characterized in that: In the step of sequentially adding the silver nitrate solution and the dispersant solution, after the silver nitrate solution is added and reacted for 3 minutes to 10 minutes, the dispersant solution is added and reacted for 2 hours to 5 hours, wherein the dispersant solution is added dropwise at a uniform speed within 2 minutes to 5 minutes.
8. A method for preparing an electromagnetic wave shielding sheet, characterized in that: The steps include: The silver powder as claimed in claim 1 or 2, an organic matrix material, a curing agent and a diluent are mixed to obtain a silver powder slurry; and then the silver powder slurry is made into an electromagnetic wave shielding sheet through a casting process.
9. An electromagnetic wave shielding sheet prepared by the method for preparing an electromagnetic wave shielding sheet as claimed in claim 8.
10. An electronic product prepared using the electromagnetic wave shielding sheet as claimed in claim 9.
Citation Information
Cited By
Double-particle-size spherical nano silver powder and preparation method and application thereof
CN122425213A